Training on Making Alternative Energy Kits to Support Independent Curriculum Learning for Physics Teachers in Nganjuk Regency - Habibbulloh, Muhammad; Imam Sucahyo; Mita Anggaryani; Abd. Kholiq; Muhammad Satriawan; Oka Saputra (Journal of Dedication in Community, 2024)
This community service activity aims to train the making of alternative energy kits to support the learning of the Merdeka curriculum, especially for grade X for physics teachers in Nganjuk district. Physics learning in the Merdeka Curriculum requires students to think critically and innovatively through a discovery process using a project-based learning model (PjBL). One of the applications of the PjBL learning model in physics is in the alternative energy material for grade X phase E. Based on observations, there is still a lack of supporting kits to support the chapter Alternative Energy. This Community Service activity is divided into several stages, namely: identification of problems and partner needs, Community Service preparation, Community Service implementation, training in making Alternative Energy kits, and evaluating the results of Community Service activities. All participants were very enthusiastic in participating in the activity. Even from the results of the response questionnaire using Google Form which was distributed to participants, it appears that the training material provided is relatively new, interesting, and inspiring. The results of the questionnaire also showed that the training material was relevant to the needs of teachers. Participants hope that similar activities can also be improved with technology-based learning media training.